Identifying and assessing windbreaks in Ford County, Kansas using object-based image analysis - Dulin, Mike W. (Kansas State University, 2009)
Windbreaks are a valuable resource in conserving soils and providing crop protection in western Kansas and other Great Plains states. Currently, Kansas has neither an up-to-date inventory of windbreak locations nor an assessment of their condition. The objective of this study is to develop remote sensing and geographic information system methods that rapidly identify and assess the condition of windbreaks in Ford County, Kansas. Ford County serves as a pilot study area for method development with the intent of transferring those methods to other counties/regions in Kansas and the Great Plains. A remote sensing technique known as object-based classification was used to classify windbreaks using color aerial photography acquired through the 2008 National Agricultural Imagery Program. Object-based classification works by segmenting imagery where areas with similar spectral, shape, and textural properties are grouped into vectors (i.e., objects) that are later used as the basis for image classification. Using this technique, 355 windbreaks, totaling nearly 1,012 acres (410 hectares), were identified in Ford County. When compared to a spatial data set of confirmed windbreak locations generated via a heads-up digitizing process, the location of windbreaks identified using object-based classification results agreed approximately 81% of the time. Mean textural and spectral values were then combined and used to place identified windbreaks into three condition categories (good, fair, and poor) using a manual classification approach. Analysis showed the area of windbreaks in good condition to be 170 hectares, with the remaining 171 hectares of windbreaks falling in the fair or poor classes. Methods detailed in this study proved successful at rapidly identifying windbreak location and for providing useful condition class results for windbreak renovation and restoration planning.
Keywords: Windbreaks; Remote Sensing; Geographic Information Systems; Object-based classification; Agriculture, Forestry and Wildlife (0478); Geography (0366); Remote Sensing (0799)